Analysis of Prospective Primary School Teachers' Innovative Ideas on How to Teach Science So that Students Enjoy It More: Analisis Ide Inovatif Calon Guru Sekolah Dasar Tentang Cara Mengajarkan IPA Agar Lebih di Senangi Oleh Siswa - Asriani, Wa; Rahmadana, Arini (IAIN Sorong, 2024)
Elementary school teachers often face challenges in teaching science in an interesting way to students, due to students' low interest in learning about science. This impacts their understanding of scientific concepts that are important for their future development. In addition, low interest in studying science can affect overall academic achievement. This research aims to find out and collect various innovative ideas from prospective elementary school teachers regarding science teaching that can increase student interest and enjoyment. If not handled well, low interest in learning science can also have a negative impact on students' ability to adapt to developments in technology and science in the modern world. This research used a qualitative method with a descriptive approach, using the entire population of student teacher candidates for Madrasah Ibtidaiyah semester 6 of IAIN Sorong and using a random sample of 18 student teacher candidates from IAIN Sorong. The research results show that there are various innovative ideas in teaching science, such as outdoor learning, the use of technology, and strategies to measure student interest. The implementation of these ideas is expected to increase interest in learning science among elementary school students, thereby helping them understand the material better and improving academic achievement.